1997
DOI: 10.1177/096120339700600307
|View full text |Cite
|
Sign up to set email alerts
|

Side-effects of intravenous cyclophosphamide pulse therapy

Abstract: We reviewed the side-effects of intravenous (i.v.) cyclophosphamide (CPM) pulse therapy in a group of 75 patients suffering from various autoimmune disorders (mostly systemic lupus erythematosus and vasculitis) who received a total of 451 i.v. CPM pulses, given on a monthly basis (mean +/- s.d. CPM dose per pulse: 764 +/- 217 mg; mean +/- s.d. follow-up period: 26.7 +/- 22.1 mon). Infection was the most common side-effect (30 episodes in 21 patients; 28% of the patients) but rarely required in-patient treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 12 publications
0
55
1
1
Order By: Relevance
“…The most important factors limiting the applicability of CP are adverse effects. As described in previous studies, the most common early adverse effects were nausea, vomiting and various infections [15,16]. All the patients who experienced nausea or vomiting were treated with standard doses of ondansetron in oral or intravenous form, which resulted in relief of the symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
“…The most important factors limiting the applicability of CP are adverse effects. As described in previous studies, the most common early adverse effects were nausea, vomiting and various infections [15,16]. All the patients who experienced nausea or vomiting were treated with standard doses of ondansetron in oral or intravenous form, which resulted in relief of the symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, her proteinuria failed to regress. Intravenous cyclophosphamide has been used widely for the treatment of patients with diffuse proliferative LN, but adverse effects such as infections have been noted (13). Recent reports have indicated that tacrolimus, an immunosuppressant agent, was an effective induction therapy for diffuse proliferative LN (14), therefore we combined tacrolimus with high-dose steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results have been conflicting, but most studies have reported IV therapy to be less effective than oral (Jabs et al 2000;Rosenbaum 1994;Ozyazgan et al 1992), while a small number have concluded that IV pulse alone or in combination with low-dose corticosteroid treatment is as effective as oral with fewer side effects and decreased mortality (Khan et al 2013;Suelves et al 2013). The SITE Study demonstrated a trend for increased cancer-related mortality, leading to the authors' suggestion that even though IV delivery may be less effective for inflammation control, it may be preferable in order to reduce the risk of malignancy (Kempen et al 2008;Pujari et al 2010;Martin et al 1997). …”
Section: Cyclophosphamidementioning
confidence: 99%